The Use of Non-Pharmacological to Decrease Anxiety and Improve the Breastfeeding Self Efficacy Postpartum Mothers: A Systematic Literature Review - Rohmatun Nazilah; Melyana Nurul Widyawati; Leny Latifah (JURNAL KEBIDANAN, 2021)
Breastfeeding mothers are critical for realizing a qualified and dignified Indonesian generation. However, mental health, such as anxiety, frequently appears on postpartum mothers during the first week of the delivery that decreases the breast milk production of postpartum mothers. It lowers the intention to breastfeed. This research aims to identify the implementation of non-pharmacological therapy to lose anxiety and improve the breastfeeding efficacy of postpartum mothers. This systematic literature review begins by searching articles, published from 2011 until 2021, via some databases, such as google scholar, national library, and sciencedirect. The applied keywords were such as non-pharmacological treatment, anxiety, breastfeeding self-efficacy, and postpartum mothers. The applied method was PRISMA. The researcher found 450 articles selected based on the keyword combinations. Then, the researchers screened the articles into 11 articles that met with the inclusion and exclusion criteria, Sinta, and DOI. The articles took the topic of non-pharmacological therapy to decrease anxiety and improve breastfeeding self-efficacy in postpartum mothers. The researcher found the non-pharmacological interventions were massage therapy, hypnotherapy, aromatherapy, progressive muscular relaxation, mother-to-baby skin contact, lactation consultation, and peer education. They were effective to lose the anxiety and improve the breastfeeding self-efficacy of postpartum mothers.